2016
DOI: 10.3390/nu8030148
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of an Oil and Wheat Flour Fortification Program on Pre-School Children and Women of Reproductive Age Living in Côte d’Ivoire, a Malaria-Endemic Area

Abstract: Anemia and micronutrient deficiencies are widespread in sub-Saharan Africa, but the impact of food fortification is still debated. The objective of this study was to estimate the iron and vitamin A status of preschool children (PSC) and women of reproductive age (WRA) in households consuming fortified oil and wheat flour. The survey was cross-sectional in a rural and an urban area. Data on demographics, socioeconomic status, and fortified foods were collected at households. Hemoglobin (Hb), retinol binding pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 14 publications
0
6
0
Order By: Relevance
“…In the Cote d'Ivoire, iron fortification of wheat flour became mandatory in 2007 as part of the fortification policy [10]. Despite its mandatory nature, subsequent surveys evaluating the impact of this policy showed that only around 50% of the flour samples complied with the mandated levels of iron fortification limiting the potential impact [11,14]. Rohner et al conclude that despite this policy, the prevalence of IDA remains high and that there is still a need for additional iron-fortified food vehicles to reduce the burden [11].…”
Section: Introductionmentioning
confidence: 99%
“…In the Cote d'Ivoire, iron fortification of wheat flour became mandatory in 2007 as part of the fortification policy [10]. Despite its mandatory nature, subsequent surveys evaluating the impact of this policy showed that only around 50% of the flour samples complied with the mandated levels of iron fortification limiting the potential impact [11,14]. Rohner et al conclude that despite this policy, the prevalence of IDA remains high and that there is still a need for additional iron-fortified food vehicles to reduce the burden [11].…”
Section: Introductionmentioning
confidence: 99%
“…A recent study demonstrated that fortification of vegetable oil with other micronutrient such as vitamin A and iron improved the nutritional status in the study participants. 34 An additional advantage offered by fortification of these other vehicles is the prevention of hypertension associated with increased salt intake. …”
Section: Way Forwardmentioning
confidence: 99%
“…Malaria infection can cause further distortion which must be taken into account (Rohner et al . ). Also of particular relevance in developing countries, intestinal helminth infections can affect nutritional status in many ways, including by reducing micronutrient absorption, increasing anaemia risk due to worms feeding on the blood and causing loss of appetite (WHO ).…”
Section: Introductionmentioning
confidence: 97%